KEKUATAN HUKUM SURAT PERNYATAAN PENGUASAAN FISIK SEBAGAI ALAS HAK PENGURUSAN HAK ATAS TANAH [Legal Enforcement of A Statement Letter of Land Utilization as the Legal Basis to Obtain Land Rights] - Gunanegara Gunanegara (Law Review, 2022)
A person or legal-person who utilises state land or customary land needs a title to be able to apply for land rights. The form and type of the title used is only accepted if it is in accordance with the regulation of UUPA juncto PP No. 24 of 1997. That norm regulated basis of land rights has changed after enactment of PP No. 18 on the year 2021. Whoever utilise of the land as be a title to apply for land rights could be proofed by a statement letter. How a legal force of statement letter to apply for land rights in land law as a legal issue of this research. Aim of the research is juridical-analysis concerning statement letter as proof of land utilisation for land rights basis. The research was conducted using normative juridical research methods, and the conclusion that the statement letter regulated by PP No. 18 of 2021 actually has a little bit of legal force, because it has a unilateral ownership claim and it is unauthentic letter.Bahasa Indonesia Abstrak: Orang yang menguasai tanah negara atau tanah adat memerlukan alas hak untuk dapat mengajukan permohonan hak atas tanah. Bentuk dan jenis alas hak yang digunakan hanya diakui jika sesuai dengan yang diatur UUPA juncto PP No. 24 Tahun 1997. Ketentuan baru soal alas hak berubah bersamaan dengan diundangkannya PP No. 18 Tahun 2021. Disebutkan bahwa penguasaan fisik atas tanah adalah alas hak untuk permohonan hak yang dibuktikan dengan surat pernyataan penguasaan fisik (SPPF). Bagaimana kekuatan hukum SPPF sebagai alas hak untuk permohonan hak ditinjau dari hukum pertanahan menjadi masalah hukum di penelitian ini. Tujuan peneltian untuk menganalisis SPPF sebagai alas hak permohonan hak atas tanah. Penelitian dilakukan dengan menggunakan metode penelitian yuridis normatif, dan kesimpulannya bahwa SPPF yang diatur PP No. 18 Tahun 2021 sejatinya mempunyai kekuatan hukum pembuktian yang tidak kuat, karena bermaterikan pengakuan sepihak dan berkualifikasi di bawah tangan.